2022
DOI: 10.1186/s12909-022-03648-5
|View full text |Cite
|
Sign up to set email alerts
|

Bridging gaps in oral health education in a medical school in the United States: a pilot study

Abstract: Background Oral health is an important component of medical education given its connection to overall health and quality of life; however, oral health is infrequently incorporated into medical school curricula in the United States. The aim of this study was to pilot a novel oral health care clerkship for United States medical students that implemented the Smiles for Life (SFL) curriculum, in-person clinical activities, and pre and post curricula assessments to assess knowledge acquisition, atti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…A plausible explanation for the difference in knowledge between the two cohorts could be that the pediatricians acquired more oral health knowledge through practice. While some medical programs have started incorporating oral health topics into their curricula, this is not true for the region in this study [ 48 , 49 ]. In any case, the results of a 2018 US study suggested that there was little acquisition of oral health knowledge over the course of pediatric residency programs [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…A plausible explanation for the difference in knowledge between the two cohorts could be that the pediatricians acquired more oral health knowledge through practice. While some medical programs have started incorporating oral health topics into their curricula, this is not true for the region in this study [ 48 , 49 ]. In any case, the results of a 2018 US study suggested that there was little acquisition of oral health knowledge over the course of pediatric residency programs [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Education also dispels myths and misconceptions, reducing dental anxiety and fostering positive attitudes toward oral health. Moreover, EIOH is not limited to the public; it is equally crucial for healthcare professionals (3)(4)(5). In other words, it is empirically sound to assert that EIOH functions as a pivotal cornerstone in the prevention of OD and the promotion of holistic health.…”
Section: Editorial On the Research Topic Education In Oral Healthmentioning
confidence: 99%